2015
DOI: 10.1097/md.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microincision Vitrectomy Surgery Using Wide-Viewing System for Complications With Ocular Sarcoidosis

Abstract: We evaluate the outcomes of microincision vitrectomy surgery (MIVS) using wide-viewing system for complications with ocular sarcoidosis resistance to medical treatment.Consecutive clinical records of 24 eyes (19 patients) with complications of ocular sarcoidosis underwent MIVS between April 2010 and December 2013 were retrospectively reviewed. MIVS and phacoemulsification were performed in 18 eyes and MIVS only in 6 eyes. Best-corrected visual acuity (BCVA), inflammation scores in the anterior segment and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The diagnostic vitrectomy used in this study was useful to rule out various etiologies causing VO and consequently allows choices of appropriate therapeutic options. [ 13 , 15 , 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic vitrectomy used in this study was useful to rule out various etiologies causing VO and consequently allows choices of appropriate therapeutic options. [ 13 , 15 , 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Best-corrected visual acuity (BCVA) was measured at the initiation using a standard Japanese visual acuity chart. The decimal BCVA was converted to the logarithm of the minimum angle of resolution (logMAR) for statistical analysis, as previously described [ 10 ]. IOP was measured by Goldmann applanation tonometry and indirect ophthalmoscopy at the initiation and each subsequent visit.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, employment of a small-gauge, cannulated vitrectomy system might also diminish secondary intraocular inflammation induced by the vitrectomy itself. Recent reports have suggested that microincision vitreous surgery can be a safe and efficacious approach for patients with uveitis [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%